A Systems Biology Approach for Studying Heterotopic Ossification: Proteomic Analysis of Clinical Serum and Tissue Samples - Crowgey, Erin L.; Wyffels, Jennifer T.; Osborn, Patrick M.; Wood, Thomas T.; Edsberg, Laura E. (Genomics, proteomics & bioinformatics, 2018)
Heterotopic ossification (HO) refers to the abnormal formation of bone in soft tissue. Although some of the underlying processes of HO have been described, there are currently no clinical tests using validated biomarkers for predicting HO formation. As such, the diagnosis is made radiographically after HO has formed. To identify potential and novel biomarkers for HO, we used isobaric tags for relative and absolute quantitation (iTRAQ) and high-throughput antibody arrays to produce a semi-quantitative proteomics survey of serum and tissue from subjects with (HO+) and without (HO−) heterotopic ossification. The resulting data were then analyzed using a systems biology approach. We found that serum samples from subjects experiencing traumatic injuries with resulting HO have a different proteomic expression profile compared to those from the matched controls. Subsequent quantitative ELISA identified five blood serum proteins that were differentially regulated between the HO+ and HO− groups. Compared to HO− samples, the amount of insulin-like growth factor I (IGF1) was up-regulated in HO+ samples, whereas a lower amount of osteopontin (OPN), myeloperoxidase (MPO), runt-related transcription factor 2 (RUNX2), and growth differentiation factor 2 or bone morphogenetic protein 9 (BMP-9) was found in HO+ samples (Welch two sample t-test; P < 0.05). These proteins, in combination with potential serum biomarkers previously reported, are key candidates for a serum diagnostic panel that may enable early detection of HO prior to radiographic and clinical manifestations.